Kerjasama Papua Nugini dan Australia dalam Kebijakan Operation Sovereign Borders - Safitri, Devi Nur; Wahyudi, Fendy Eko (Journal of International Relations, 2020)
In terms of immigration, Papua New Guinea and Australia have committed to jointly face human smuggling actions, that are closely related to the arrival of refugees and asylum seekers. However, the collaboration between the two countries under the Pacific Solution and PNG Solution policies has caused many disadvantages for Papua New Guinea. Strangely, in 2013, Papua New Guinea signed the agreement documents to collaborate on immigration with Australia. The purpose of this study is to find out the reason behind the availability of Papua New Guinea who are willing to continue their cooperation with Australia on immigration, under Operation Sovereign Borders policy. This research uses the theory of institutional liberalism which is in the neoliberal paradigm. Therefore, the results of this study indicate that the reason for the availability of Papua New Guinea to cooperate with Australia, as evidenced by the signing of cooperation agreement documents between the two nation is, if Papua New Guinea is willing to cooperate, the country will achieve its interests as stated in Papua New Guinea Vision 2050.